DESAIN DAN UJI COBA LEMBAR KERJA PESERTA DIDIK ELEKTRONIK (E-LKPD) BERBASIS DAILY LIFE PADA MATERI HIDROKARBON - dila agusti; yuni fatisa (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2021)
AbstractThe lack of media variation used constituted a background of this research.  Student concept comprehension was not yet supported, and the media often used were student conventional workbook and exercises. This research aimed at developing daily life-based student electronic workbook on Hydrocarbon Compounds lesson by using Borg and Gall development model to know validity and practicality levels of the workbook.  It was Research and Development (R&D). 5 of 10 steps in Borg and Gall development model were used in this research, they were collecting data, planning, developing a product, preliminary testing.  Testing was conducted to a chemistry subject teacher and 10 of the eleventh-grade students of MIPA at Senior High School of Islam As-Shofa Pekanbaru.  The data obtained were analyzed by using qualitative and quantitative descriptive analysis techniques.  Daily life-based student electronic workbook on Hydrocarbon Compounds lesson was tested very valid with the percentages 90% by media experts and 92% by material experts, the percentage of practicality test by teacher was 91.42%, and the workbook got good student responses.  Based on these findings, it could be concluded that daily life-based student electronic workbook on Hydrocarbon Compounds lesson was valid and practical, so it was proper to be used as a learning media at school. Keywords:    Student Electronic Workbook, Daily Life, Hydrocarbon Compounds Lesson